Monomer composition for contact lens, polymer for contact lens, and contact lens
By using monomer compositions containing phosphocholine bases and other monomers, the problem of the inability of traditional contact lenses to provide effective oxygen and surface treatment is solved, and good wear comfort and corneal health protection is achieved.
Patent Information
- Application Number
- CN202380066583.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-15
- Filing Date
- 2023-09-13
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional soft contact lenses cannot effectively provide the oxygen required by the cornea, resulting in the impact of corneal health when worn for a long time. At the same time, their surface treatment is complex and difficult to achieve good wearing comfort and stain resistance.
The contact lenses are manufactured through the polymer polymer polymer polymerization process using a monomer containing a phosphocholine group, a silicone macromonomer, a hydroxyl hydrophilic monomer, an amide hydrophilic monomer and a crosslinking agent to achieve good surface hydrophilicity, antifouling and oxygen permeability.
The contact lenses are achieved without surface treatment and exhibit very good hydrophilicity, moisture content, oxygen permeability and stain resistance, improving wear comfort and reducing the risk of corneal health.
Smart Images

Figure BDA0005314187230000041 
Figure BDA0005314187230000042 
Figure BDA0005314187230000043
Abstract
Description
Technical Field
[0001] The present invention relates to a monomer composition for contact lenses, a polymer for contact lenses and a contact lens. Background Art
[0002] Contact lenses have been used to improve vision since the 1950s. The first contact lenses were hard contact lenses, and although these lenses are still in use today, they are not widely used due to their poor initial comfort. In the 1960s, soft contact lenses made of hydrogels were developed, and due to their ease of use and convenience, the number of wearers wearing them has increased rapidly, and soft contact lenses are now widely used by the public.
[0003] However, conventional soft contact lenses cannot provide a sufficient amount of oxygen to the cornea of the eye, thus causing safety issues when wearing soft contact lenses for a long time. This is because the cornea does not receive oxygen from the blood, unlike other tissues. When not enough oxygen reaches the cornea, there is a possibility of corneal damage, and prolonged hypoxia is not preferred for the cornea. On the other hand, in recent years, in order to solve this problem, silicone hydrogel contact lenses have been developed as contact lenses with improved safety. Silicone hydrogel contact lenses allow sufficient oxygen to penetrate the contact lenses to reach the cornea, thereby minimizing adverse effects on corneal health.
[0004] However, since silicone hydrogel contact lenses contain hydrophobic silicone monomers or macromers, it is difficult to obtain contact lenses with good wearing comfort using only these compounds, and hydrophilization treatment is required. In addition, lipids in tear fluid can be deposited on the worn lenses and can cause discomfort and be detrimental to the eye health of the wearer, and contact lenses that also have excellent antifouling properties are required.
[0005] As a method of subjecting a contact lens to a hydrophilization treatment, for example, a method of imparting hydrophilicity and antifouling properties to the surface of a contact lens by graft-polymerizing a hydrophilic monomer into the surface of a contact lens that has been subjected to a plasma treatment has been disclosed (Patent Document 1). In addition, a method of manufacturing a contact lens having excellent hydrophilicity and lubricity by coating the surface of a contact lens with a polymer has been disclosed (Patent Document 2). These surface treatments require complicated steps, which are undesirable for large-scale production.
[0006] Patent Documents 3 and 4 disclose compositions containing MPC and a silicone-containing itaconate diester monomer having a primary hydroxyl group, and disclose that the polymer of the composition can be used for contact lenses. The contact lens disclosed in Patent Document 3 exhibits good results in terms of hydrophilicity and oxygen permeability of the lens surface, while the contact lens according to Patent Document 4 exhibits good results in terms of elongation at break and peelability in addition to these. In these patent documents, contact lenses can be easily obtained without surface treatment, but antifouling properties are not considered.
[0007] Prior art documents
[0008] Patent Literature
[0009] Patent Document 1: JP2003-215509A
[0010] Patent Document 2: JP2018-022174A
[0011] Patent Document 3: WO2018 / 135421
[0012] Patent Document 4: WO2020 / 054711 Summary of the invention
[0013] The purpose to be achieved by the present invention
[0014] An object of the present invention is to provide a monomer composition for contact lenses and a polymer for contact lenses, which can be used to produce contact lenses that provide excellent wearing comfort to the wearer due to good surface hydrophilicity, good antifouling properties (coatability) and good oxygen permeability, and to provide contact lenses.
[0015] Solutions to the problem
[0016] As a result of intensive studies, the inventors of the present invention have found that the above-mentioned problems can be solved by using a composition comprising a phosphorylcholine group-containing monomer, a phosphorylcholine group-containing silicone macromer, a silicone monomer or macromer other than the phosphorylcholine group-containing silicone macromer represented by the following formula (2), a hydroxyl group-containing hydrophilic monomer, an amide group-containing hydrophilic monomer and a crosslinking agent as a composition for contact lenses, thereby completing the present invention.
[0017] That is, the present invention is as follows.
[0018] 1. A monomer composition for contact lenses, comprising:
[0019] (A) a phosphorylcholine group-containing monomer represented by the following formula (1);
[0020] (B) a phosphorylcholine group-containing organosilicon macromer represented by the following formula (2);
[0021] (C) an organosilicon monomer or macromer other than the organosilicon macromer containing a phosphorylcholine group represented by formula (2);
[0022] (D) one or more hydroxyl-containing hydrophilic monomers selected from the group consisting of hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyethyl (meth)acrylamide, ethylene glycol monovinyl ether, glyceryl methacrylate and diethylene glycol monovinyl ether;
[0023] (E) one or more amide group-containing hydrophilic monomers, wherein the one or more amide group-containing hydrophilic monomers are selected from the group consisting of N-vinyl-2-pyrrolidone, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-methyl-N-vinylacetamide and N-vinylacetamide; and
[0024] (F) a cross-linking agent, wherein
[0025] Relative to 100% by mass of the total amount of components (A) to (F) in the composition according to the present invention, the content of component (A) is 5% to 25% by mass, the content of component (B) is 10% to 60% by mass, the content of component (C) is 5% to 40% by mass, the content of component (D) is 5% to 40% by mass, the content of component (E) is 0% to 20% by mass, and the content of component (F) is 0% to 2.5% by mass.
[0026] [Chemical formula 1]
[0027]
[0028] [In formula (1), R 1 H or CH 3 , and W 1 O or NR 4 , where R 4 is H or an alkyl group having 1 to 4 carbon atoms],
[0029] [Chemical formula 2]
[0030]
[0031] [In formula (2), R 1 H or CH 3 , W 1 O or NR 4 , where R 4is H or an alkyl group having 1 to 4 carbon atoms, a is an integer from 1 to 100, and A 1 It is expressed by formula (3)],
[0032] [Chemical formula 3]
[0033] -YZ···Formula (3)
[0034] [In formula (3), Y is represented by formula (4), and Z is a phosphorylcholine group represented by formula (6)],
[0035] [Chemical formula 4]
[0036]
[0037] [In the formula, b is 2 or 3, and c is 0 or 1],
[0038] [Chemical formula 5]
[0039]
[0040] 2. The monomer composition for contact lenses according to 1 above, wherein the component (C) is a hydroxyl-containing silicone monomer represented by the following formula (9) or (10).
[0041] [Chemical formula 6]
[0042]
[0043] [Chemical formula 7]
[0044]
[0045] 3. The monomer composition for contact lenses according to 1 or 2 above, wherein, in the monomer composition for contact lenses comprising the components (A) to (F), the proportion of phosphorylcholine groups is 10% by mass or more, and the proportion of silicon is 10% or more.
[0046] 4. A polymer for contact lenses, which is a polymer of the monomer composition for contact lenses according to 1 or 2 above.
[0047] 5. A contact lens comprising:
[0048] A hydrate of the polymer for contact lenses according to 4 above.
[0049] 6. The contact lens according to 5 above, wherein the oxygen permeability coefficient Dk of the contact lens is 50×10 -11 (cm 2 / sec)·(mLO 2 / mL×mmHg) or above.
[0050] Effects of the Invention
[0051] The contact lens according to the present invention is produced using the monomer composition for contact lenses according to the present invention, and thus can simultaneously exhibit very good surface hydrophilicity, very good water content, good coatability, and good oxygen permeability. DETAILED DESCRIPTION
[0052] Hereinafter, the present invention will be described in more detail.
[0053] In this specification, when describing the preferred numerical range (e.g., concentration or weight average molecular weight range, etc.) in stages, each lower limit and upper limit can be independently combined. For example, in the description of "preferably 10 or more, more preferably 20 or more, and preferably 100 or less, more preferably 90 or less", "preferably lower limit: 10" and "preferably upper limit: 90" can be combined as "10 or more and 90 or less". In addition, the description of "preferably 10 to 100, more preferably 20 to 90" can also be combined as "10 to 90" in the same way.
[0054] In the present specification, “(meth)acrylic acid” refers to acrylic acid or methacrylic acid, “(meth)acryloyl” refers to acryl or methacryloyl, “(meth)acrylate” refers to acrylate or methacrylate, “(meth)acrylamide” refers to acrylamide or methacrylic acid amide, and “(meth)acrylate ester” refers to acrylic ester or methacrylate ester.
[0055] In this specification, hydrophilicity refers to the ability of a contact lens surface to retain a water film.
[0056] In the present specification, coatability (antifouling property) refers to an effect of reducing the amount of adhesion of a hydrophobic substance such as lipid adhering to a contact lens to a contact lens.
[0057] In the present specification, oxygen permeability refers to an oxygen permeability coefficient measured according to the method described in ISO 18369-4.
[0058] <Monomer Composition for Contact Lenses>
[0059] The monomer composition for contact lenses according to the present invention contains components (A) to (F) which will be described later as essential components, and may further contain component (G), component (H) and component (I) which will be described later as optional components.
[0060] Hereinafter, the monomer composition for contact lenses according to the present invention may be simply referred to as the composition or composition according to the present invention. The polymer for contact lenses as a polymer for the monomer composition for contact lenses according to the present invention may be simply referred to as the polymer or polymer according to the present invention. The contact lens containing the hydrate of the polymer for contact lenses according to the present invention may be simply referred to as the contact lens or contact lens according to the present invention.
[0061] (A): Monomer containing phosphorylcholine group
[0062] Component (A) is a phosphorylcholine group-containing monomer represented by the following formula (1).
[0063] Suitable examples include W 1 2-(Meth)acryloyloxyethyl(2-(trimethylammonium)ethyl)phosphate and W 1 NR 4 And R 4 2-(Meth)acrylamideethyl(2-(trimethylammonio)ethyl)phosphate wherein R 1 is methyl and W 1 is 2-methacryloyloxyethyl (2-(trimethylammonio)ethyl) phosphate, and R 1 is a hydrogen atom, W 1 NR 4 And R 4 2-Acrylamidoethyl (2-(trimethylammonio)ethyl) phosphate is H. From the viewpoint of availability, 2-methacryloyloxyethyl (2-(trimethylammonio)ethyl) phosphate (MPC: (2-methacryloyloxyethyl) phosphorylcholine) is more preferred.
[0064] Component (A) is capable of improving the hydrophilicity and lubricity on the surface of the contact lenses according to the invention.
[0065] [Chemical formula 8]
[0066]
[0067] In formula (1), R 1 H or CH 3 , and W 1 O or NR 4 , where R 4 is H or an alkyl group having 1 to 4 carbon atoms.
[0068] The content of component (A) relative to 100 mass % of the total amount of components (A) to (F) in the composition according to the present invention is 5 mass % to 25 mass %, preferably 7 mass % to 20 mass %, and more preferably 8 mass % to 18 mass %.
[0069] When the content is less than 5% by mass, sufficient hydrophilicity may not be imparted to the surface of the contact lens. When the content is greater than 25% by mass, it is difficult to dissolve component (A) in the composition, and there is a concern that the oxygen permeability of the contact lens may decrease.
[0070] (B): Silicone macromer containing phosphorylcholine
[0071] Component (B) is a phosphorylcholine group-containing silicone macromer represented by the following formula (2), and is a component for improving the oxygen permeability, transparency, hydrophilicity and lubricity of the contact lens according to the present invention.
[0072] The content of component (B) is 10% to 60% by mass, preferably 15% to 55% by mass, and more preferably 20% to 45% by mass, relative to 100% by mass of the total amount of components (A) to (F) in the composition according to the present invention. When the content is less than 10% by mass, there is a possibility that the transparency of the contact lens is reduced, and there is a possibility that the oxygen permeability of the contact lens is reduced. When the content is more than 60% by mass, there is a possibility that the composition according to the present invention has a high viscosity and is difficult to handle.
[0073] [Chemical formula 9]
[0074]
[0075] In formula (2), R 1 H or CH 3 , W 1 O or NR 4 , where R 4 is H or an alkyl group having 1 to 4 carbon atoms, a is an integer from 1 to 100, and A 1 It is expressed by formula (3).
[0076] a is not particularly limited as long as it is within the range of 1 to 100, and is preferably 2 to 50, more preferably 2 to 40, and still more preferably 2 to 30.
[0077] [Chemical formula 10]
[0078] -YZ···Formula (3)
[0079] In formula (3), Y is represented by formula (4), and Z is a phosphorylcholine group represented by formula (6).
[0080] [Chemical formula 11]
[0081]
[0082] In the formula, b is 2 or 3, and c is 0 or 1.
[0083] [Chemical formula 12]
[0084]
[0085] An example of an embodiment of (B) is a compound represented by the following formula (2-1). Note that a is an integer of 1 to 100.
[0086] [Chemical formula 13]
[0087]
[0088] (C): an organosilicon monomer or macromonomer other than the organosilicon macromonomer containing a phosphorylcholine group represented by formula (2)
[0089] Component (C) is a silicone monomer or macromer other than the silicone macromer containing a phosphorylcholine group represented by formula (2). Component (C) is a component for improving the oxygen permeability of a contact lens obtained from the composition according to the present invention, and may be one type or a mixture of two or more types.
[0090] The content of component (C) is 5% to 40% by mass, preferably 8% to 30% by mass, and more preferably 10% to 25% by mass, relative to 100% by mass of the total amount of components (A) to (F) in the composition according to the present invention. When the content is less than 5% by mass, sufficient oxygen permeability may not be obtained. When the content is more than 40% by mass, there is a possibility that the hydrophilicity of the contact lens is reduced.
[0091] An example of an embodiment of the component (C) is a compound represented by the following formula (9), formula (10), formula (11) or formula (12).
[0092] [Chemical formula 14]
[0093]
[0094] [Chemical formula 15]
[0095]
[0096] [Chemical formula 16]
[0097]
[0098] [Chemical formula 17]
[0099]
[0100] (D): Hydrophilic monomer containing hydroxyl groups
[0101] Component (D) is one or more hydroxyl-containing hydrophilic monomers selected from the group consisting of hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyethyl (meth)acrylamide, ethylene glycol monovinyl ether, glyceryl methacrylate and diethylene glycol monovinyl ether. Component (D) is a component for improving the transparency of the composition according to the present invention and the transparency of the contact lens obtained from the composition according to the present invention, and may be any one type of these monomers or a mixture of two or more types.
[0102] Specific examples of component (D) include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylamide, ethylene glycol monovinyl ether, and diethylene glycol monovinyl ether.
[0103] The content of component (D) is 5% to 40% by mass, preferably 10% to 35% by mass, and more preferably 15% to 30% by mass, relative to 100% by mass of the total amount of components (A) to (F) in the composition according to the present invention. When the content is less than 5% by mass, there is a possibility that component (A) is difficult to dissolve in the composition, and there is a possibility that the transparency of the contact lens is reduced. When the content is more than 40% by mass, sufficient oxygen permeability may not be obtained.
[0104] (E): Hydrophilic monomer containing amide group
[0105] Component (E) is one or more amide-containing hydrophilic monomers selected from the group consisting of N-vinylpyrrolidone (N-vinyl-2-pyrrolidone), N,N-dimethylacrylamide, N,N-diethylacrylamide, N-methyl-N-vinylacetamide and N-vinylacetamide.
[0106] Component (E) is a component for adjusting physical properties such as water content in the composition according to the present invention, and may be any one type or a mixture of two or more types of these monomers.
[0107] The content of component (E) is preferably 0% to 20% by mass or 0.01% to 20% by mass, preferably 18% by mass or less, and more preferably 15% by mass or less, relative to 100% by mass of the total amount of components (A) to (F) in the composition according to the present invention. When the content is more than 20% by mass, sufficient oxygen permeability may not be obtained, or antifouling properties may decrease.
[0108] (F): Cross-linking agent
[0109] Component (F) is a crosslinking agent. It can be admixed to adjust the physical properties of the contact lenses according to the invention.
[0110] Examples of component (F) include crosslinking agents such as ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, 2-(2-vinyloxyethoxy)ethyl (meth)acrylate, divinylbenzene, allyl (meth)acrylate, and polydimethylsiloxane dimethacrylate.
[0111] Component (F) may be any one type or a mixture of two or more types among these examples.
[0112] The content of component (F) is preferably 0% by mass to 2.5% by mass or 0.005% by mass to 2.5% by mass, more preferably 0.1% by mass to 2.0% by mass, and more preferably 0.2% by mass to 1.5% by mass, relative to 100% by mass of the total amount of components (A) to (F) in the composition according to the present invention. When the content is more than 2.5% by mass, there is a concern that the contact lens may be fragile.
[0113] (G): polymerization initiator
[0114] The composition according to the present invention may be a composition containing a polymerization initiator as an optional component (G). In the case of containing component (G), care must be taken in the storage of the composition according to the present invention, etc., and there is an advantage that the polymer for contact lenses according to the present invention can be easily obtained with stable quality by simply heating the composition according to the present invention, etc. Component (G) is not particularly limited, and any known thermal polymerization initiator or photopolymerization initiator can be used.
[0115] Examples of the thermal polymerization initiator include azo-based polymerization initiators such as 2,2'-azobis(isobutyronitrile), dimethyl 2,2-azobis(2-methylpropionate), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] disulfate dihydrate, 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] dihydrate, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] 2,2'-azobis(1-imino-1-pyrrolidinyl-2-methylpropane) dihydrochloride, 2,2'-azobis[2-methyl-N-{1,1-bis(hydroxymethyl)-2-hydroxyethyl}propionamide], 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis(2-methylpropionamidine) dihydrochloride and 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide]; and peroxide-based polymerization initiators such as benzoyl peroxide, tert-butyl hydroperoxide, isopropylbenzene hydroperoxide, lauroyl peroxide, tert-butyl peroxyhexanoate and 3,5,5-trimethylhexanoyl peroxide.
[0116] Examples of photopolymerization initiators include 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzyldiphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, benzoin methyl ester, camphorquinone, and ethyl 4-(N,N-dimethylamino)benzoate. In addition, examples of photopolymerization initiators represented by trade names include Irgacure 819, Irgacure 1700, Irgacure 1800, Irgacure 819, Irgacure 1850, Darocur 1173, and Darocur 2959. Component (G) may be any one type of these photopolymerization initiators or a mixture of two or more types.
[0117] Component (G) may be any one type or a mixture of two or more types of these thermal polymerization initiators.
[0118] In the case where component (G) is contained, its content is preferably 0.01 to 3 parts by mass, and more preferably 0.1 to 2 parts by mass, relative to 100 parts by mass of the total amount of components (A) to (F) in the composition according to the present invention. When the content is less than 0.01 parts by mass, there is a concern that the polymerizability of the monomers in the composition is insufficient, and the advantage of mixing component (G) is not obtained. When the content is more than 3 parts by mass, there is a concern that the reaction decomposition product of component (G) is not sufficiently removed by extraction when washing the polymer for contact lenses obtained by polymerization to produce contact lenses.
[0119] (H): Monomers other than (A) to (F)
[0120] Component (H) is a monomer other than (A) to (F). Component (H) is an optional component, and can be mixed for the purpose of adjusting the physical properties of the contact lens according to the present invention.
[0121] Examples of component (H) include: hydrophilic monomers such as N-vinylpiperidin-2-one, N-vinyl-ε-caprolactam, N-vinyl-3-methyl-2-caprolactam, acrylamide, N-isopropylacrylamide, acryloylmorpholine, N-vinylformamide, (meth)acrylic acid, 2-methacryloyloxyethylsuccinate, methoxypolyethylene glycol methacrylate and methoxyethyl(meth)acrylate; and hydrophobic monomers such as methyl(meth)acrylate, ethyl(meth)acrylate, butyl(meth)acrylate and isobornyl(meth)acrylate.
[0122] Component (H) may be any one type of these or a mixture of two or more types.
[0123] In the case where component (H) is contained, the amount of component (H) is preferably 20 parts by mass or less, more preferably 18 parts by mass or less, and still more preferably 15 parts by mass or less, relative to 100 parts by mass of the total amount of components (A) to (F) in the composition according to the present invention. When the content of component (H) is more than 20 parts by mass, there is a concern that the transparency and durability of the contact lens are reduced.
[0124] (I) Solvent
[0125] Component (I) is a solvent having a hydroxyl group. Component (I) is an optional component and may be added for the purpose of improving the solubility of component (A) in the composition according to the present invention. Specifically, the mixing of component (I) has the advantage of increasing the dissolution rate of component (A) in the composition according to the present invention to promote dissolution.
[0126] Examples of component (I) include ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, tert-butyl alcohol, 1-pentanol, 2-pentanol, tert-pentanol, 1-hexanol, 1-octanol, 1-decanol, 1-dodecanol, glycolic acid, lactic acid, ethylene glycol, propylene glycol and butylene glycol. Component (I) can be any one type of these solvents or a mixture of two or more types. Preferred are ethanol, 1-propanol, 2-propanol, 1-hexanol and propylene glycol.
[0127] In the case where component (I) is contained, its content is not particularly limited, and is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and still more preferably 10 parts by mass or less, relative to 100 parts by mass of the total amount of components (A) to (F) in the composition according to the present invention. It is particularly preferred that the solvent is not mixed.
[0128] (Other components)
[0129] The composition according to the present invention may further contain components other than the above components within the scope that the purpose of the present invention is not affected. Examples of other components include polymerizable ultraviolet absorbers and polymerizable dyes as colorants, etc. When the ultraviolet absorber is mixed, the contact lens according to the present invention can reduce the eye burden caused by ultraviolet light from sunlight, etc. In addition, when the dye is mixed, the contact lens according to the present invention can become a colored contact lens.
[0130] The content of other components in the composition according to the present invention is preferably 7 parts by mass or less, more preferably 5 parts by mass or less, and still more preferably 3 parts by mass or less, relative to 100 parts by mass of the total amount of components (A) to (I) in the composition according to the present invention.
[0131] (Properties of the composition according to the present invention)
[0132] The composition according to the present invention (specifically, a monomer composition for contact lenses comprising (A) to (F) and an additional component (H)) has a phosphorylcholine group ratio of 10% by mass or more and a silicon ratio of 10% or more. As shown in Table 1 below, within these ranges, the effects of the present invention can be achieved.
[0133] <Method for producing the composition according to the present invention>
[0134] The method for producing the composition according to the present invention is not particularly limited, and the composition can be produced by charging the respective components in an agitation (mixing) device in any order or all at once and stirring and mixing the components at a temperature of 40° C. or less until uniform. However, in the case where component (G) is included, in order to avoid initiation of polymerization during mixing, when component (G) is a thermal polymerization initiator, the components are preferably mixed at a temperature of 40° C. or less and 10° C. or more lower than the 10-hour half-life temperature of the initiator, and when component (G) is a photopolymerization initiator, the components are preferably mixed in a light-shielded state.
[0135] <Method for producing the polymer according to the present invention>
[0136] An embodiment of a method for producing a polymer according to the present invention will be described. Note that the production method described below is one embodiment for obtaining a polymer according to the present invention, and the polymer according to the present invention is not limited to the polymer obtained by the production method.
[0137] The polymer can be produced by using a mold (metal mold) having a hydrophobic surface made of polypropylene or the like, filling the mold with the composition of the present invention, and performing polymerization. In the case of a composition not containing component (G), a polymerization initiator similar to component (G) is added to the composition in an amount similar to component (G), and the composition is dissolved to fill the mold.
[0138] In the case of polymerization using a thermal polymerization initiator, the polymerization is performed at a temperature between 45° C. and 140° C. suitable for the thermal polymerization initiator contained for 1 hour or more.
[0139] In the case of polymerization using a photopolymerization initiator, the photopolymerization initiator is subjected to ultraviolet light at a wavelength suitable for the photopolymerization initiator contained in the reaction mixture at 0.3 mW / cm 2 The above irradiance is irradiated to perform polymerization for more than 5 minutes. After the polymerization is completed, the manufactured polymer is taken out from the mold.
[0140] The polymerization atmosphere is not particularly limited, and an inert gas atmosphere such as nitrogen or argon is preferred from the viewpoint of increasing the polymerization rate. Examples of methods using an inert gas atmosphere include inflating the composition with an inert gas, placing a site where a mold is filled with the composition in an inert gas atmosphere, and performing polymerization under the inert gas atmosphere.
[0141] The pressure in the mold may be atmospheric pressure to slight pressure, and in the case of polymerization under an inert gas atmosphere, the gauge pressure is preferably 1 kgf / cm 2 the following.
[0142] <Method for manufacturing contact lens according to the present invention>
[0143] An embodiment of a method for producing a contact lens according to the present invention will be described. Note that the production method described below is one embodiment for obtaining a contact lens according to the present invention, and the contact lens according to the present invention is not limited to a contact lens obtained by the production method.
[0144] The contact lens according to the present invention is preferably a silicone hydrogel contact lens, which is a hydrate of the polymer according to the present invention. Here, "hydrate" means containing water, and the contact lens according to the present invention (silicone hydrogel contact lens according to the present invention) is a contact lens in which the polymer contains water and is in the form of a hydrogel.
[0145] The water content (ratio of water to the total mass of the contact lens) of the contact lens according to the present invention is preferably 35% or more and 60% or less, and more preferably 40% or more and 55% or less. When the water content is less than 35%, there is a concern that the lens is hard, and when the water content is more than 60%, there is a concern that the oxygen permeability is reduced.
[0146] In this specification, "silicone hydrogel" refers to a hydrogel having an organosilicon portion (siloxane bond) in the polymer. Since the composition according to the present invention contains components (B) and (C), the polymer of the composition has an organosilicon portion therein and forms a silicone hydrogel when hydrated (by containing water).
[0147] Since the polymer according to the present invention may contain unreacted substances, by-products and the like and (I) a solvent as an optional component, the polymer may be purified by washing and the like before hydration.
[0148] One of the washing methods is washing with a solvent. As a solvent, for example, water, methanol, ethanol, 1-propanol, 2-propanol, ethylene glycol, propylene glycol, butanediol or a mixture thereof can be used. Washing can be carried out, for example, by dipping the polymer according to the present invention in the above-mentioned solvent at 10°C to 40°C for 10 minutes to 5 hours, and then dipping the polymer in water for 10 minutes to 5 hours. In addition, between the washing with a solvent and the washing with water, washing by immersing the polymer in an aqueous solution with a solvent concentration of 20% to 50% by mass for 10 minutes to 5 hours can be added, or these washing steps can be performed multiple times. As water, purified water such as distilled water, ion exchange water and RO water, as well as water for injection, etc. are preferred.
[0149] The polymer according to the present invention purified by washing can be immersed in physiological saline and hydrated to obtain a contact lens. As the physiological saline, borate buffered physiological saline or phosphate buffered physiological saline can be used. Since physiological saline is used in the solution for storing soft contact lenses, the polymer can be immersed in the solution for storing soft contact lenses to be hydrated. The physiological saline preferably has an osmotic pressure of 250mOsm / kg to 400mOsm / kg.
[0150] <Properties of the contact lens according to the present invention>
[0151] The contact lenses according to the invention preferably have a 50×10 -11 (cm 2 / sec)·(mLO 2 As shown in Table 1 below, within these ranges, the effects of the present invention can be achieved.
[0152] In the contact lens according to the present invention, "very good hydrophilicity" means that the water break-up time (WBUT) is preferably 10 seconds or more in the evaluation described in detail in the Examples, although the numerical value is not particularly limited.
[0153] “Very good moisture content” means, although the numerical value is not particularly limited, a moisture content of preferably 40% or more and 55% or less in the evaluation described in detail in the Examples.
[0154] “Very good oxygen permeability” and “good oxygen permeability” mean that, although there is no particular limitation on the numerical value, in the oxygen permeability measurement described in detail in the Examples, oxygen permeability coefficients of “70 or more” and “50 or more to less than 70” are respectively preferred.
[0155] “Very good coatability” and “good coatability” mean, although the numerical values are not particularly limited, antifouling properties of “less than 0.05” and “0.05 or more to less than 0.10” are respectively preferred in the evaluation described in detail in the Examples.
[0156] Example
[0157] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited thereto. First, the components of the compositions used in Examples and Comparative Examples are as follows.
[0158] (A): Monomer containing phosphorylcholine group
[0159] MPC: (2-methacryloyloxyethyl)phosphocholine
[0160] (B): Silicone macromer containing phosphorylcholine
[0161] ·SiPC1: a compound represented by formula (2-1) {a=6}
[0162] ·SiPC2: a compound represented by formula (2-1) {a=19}
[0163] ·SiPC3: A compound represented by formula (2-1) {a=34}
[0164] (C): Silicone monomer
[0165] ·ETS: a compound represented by formula (9)
[0166] ·SiGMA: a compound represented by formula (10)
[0167] MCR-M11: A compound represented by formula (11)
[0168] ·TRIS: a compound represented by formula (12)
[0169] (D): Hydrophilic monomer containing hydroxyl groups
[0170] HEMA: 2-Hydroxyethyl Methacrylate
[0171] HBMA: 2-Hydroxybutyl Methacrylate
[0172] (E): Hydrophilic monomer containing amide group
[0173] NVP: N-vinyl pyrrolidone
[0174] (F): Cross-linking agent
[0175] ·TEGDMA: Tetraethylene glycol dimethacrylate
[0176] TMPTMA: Trimethylolpropane trimethacrylate
[0177] (G): polymerization initiator
[0178] ·AIBN:2,2'-azobis(isobutyronitrile)
[0179] I-819: Bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide
[0180] (I) Solvent
[0181] EtOH: ethanol
[0182] NPA: 1-propanol (n-propanol)
[0183] [Synthesis Example 1-1] Synthesis of an intermediate compound represented by formula (2-B) {a:6}
[0184] In 43.6 g of tetrahydrofuran, 10.8 g (49.4 mmol) of 3-(chlorodimethylsilyl)propyl methacrylate was dissolved, and 2.36 g (98.5 mmol) of lithium hydroxide was added thereto. After 30 minutes, 43.6 g of heptane was added and pressure filtration was performed to remove insoluble matter. (Through this reaction, a silanol group-containing compound having a vinyl group was obtained.)
[0185] To the filtrate from the pressure filtration was added 71.2 g of tetrahydrofuran and subsequently 22.0 g (98.8 mmol) of hexamethylcyclotrisiloxane. Subsequently, the entire amount of the catalyst solution (made in another flask by dissolving 0.74 g of diazabicycloundecene in 7.52 g of tetrahydrofuran) was added. After 4 hours, 6.60 g of triethylamine was added and 5.14 g of chlorodimethylsilane was added to stop the reaction.
[0186] The reacted solution was concentrated using an evaporator, diluted with heptane, and then washed with ion exchange water. The heptane layer was collected, dehydrated using sodium sulfate, and finally concentrated using an evaporator to obtain 26.2 g of an intermediate compound represented by formula (2-B) {a:6}.
[0187] [Chemical formula 18]
[0188]
[0189] [Synthesis Example 1-2] Synthesis of the intermediate compound represented by formula (2-B) {a:19}
[0190] In the same manner as in Synthesis Example 1-1, the amount of hexamethylcyclotrisiloxane charged was changed to obtain an intermediate compound represented by Formula (2-B) {a: 19}.
[0191] [Synthesis Example 1-3] Synthesis of the intermediate compound represented by formula (2-B) {a:34}
[0192] In the same manner as in Synthesis Example 1-1, the amount of hexamethylcyclotrisiloxane charged was changed to obtain an intermediate compound represented by Formula (2-B) {a:34}.
[0193] [Synthesis Example 2-1] Synthesis of a compound represented by formula (2-1) {a:6}
[0194] In 5.40g of 2-propanol and 3.00g of heptane, 3.00g of the compound represented by formula (2-B) {a:6} obtained in Synthesis Example 1-1 and 1.36g of 2-(2-propenyloxy)ethyl-2-(trimethylammonium)ethyl phosphate (obtained by the synthesis method described in WO2019 / 194264), and then 55μL of hexachloroplatinic acid hexahydrate (manufactured by Tokyo Chemical Industry Co., Ltd.) adjusted to 4% by weight of 2-propanol solution was added thereto, and hydrosilylation reaction was carried out at 75°C for 4 hours. 0.01g of activated carbon was added, the mixture was stirred for 30 minutes, and the activated carbon was removed by pressure filtration.
[0195] 18.0 g of ion exchange water, 6.00 g of ethanol, 24.0 g of ethyl acetate and 12.0 g of heptane were mixed and stirred. After standing, the mixture was separated into two layers, and the lower layer was discarded. Thereafter, the mixture was further purified with ion exchange water and ethyl acetate, and then concentrated using an evaporator to obtain 5.0 g of a transparent viscous substance.
[0196] 1 H NMR analysis showed that the compound was of formula (2-1) {a:6}.
[0197] Synthesis Example 2-1 1 The assignment results of H NMR analysis are shown below.
[0198] 1 H NMR (DMSO-d6): δ=0.0ppm (Si- CH 3 ), 0.5ppm(Si- CH 2 -), 1.5 to 1.8 ppm (-CH 2 - CH 2 -CH 2 -), 1.9ppm(-C-CH 3 ), 3.2ppm(N- CH 3 ), 3.3 to 3.8 ppm (O- CH 2 -, N- CH 2 -), 4.0 to 4.5 ppm (C(=O)-O- CH 2 -,-PO- CH 2 -), 5.6ppm, 6.1ppm( CH 2 =C-)
[0199] [Synthesis Example 2-2] Synthesis of the compound represented by formula (2-1) {a:19}
[0200] Synthesis was performed in the same manner as in Synthesis Example 2-1 except that the intermediate compound represented by formula (2-B) {a:19} obtained in Synthesis Example 1-2 was used.
[0201] 1 H NMR analysis showed that the compound was of formula (2-1) {a:19}.
[0202] Synthesis Example 2-2 1 The assignment results of H NMR analysis are shown below.
[0203] 1 H NMR (DMSO-d6): δ=0.0ppm (Si- CH 3 ), 0.5ppm(Si- CH 2 -), 1.5 to 1.8 ppm (-CH 2 - CH 2 -CH 2 -), 1.9ppm(-C-CH 3 ), 3.2ppm(N- CH 3 ), 3.3 to 3.8 ppm (O- CH 2 -, N- CH 2 -), 4.0 to 4.5 ppm (C(=O)-O- CH 2 -,-PO- CH 2 -), 5.6ppm, 6.1ppm( CH 2 =C-)
[0204] [Synthesis Example 2-3] Synthesis of the compound represented by formula (2-1) {a:34}
[0205] Synthesis was performed in the same manner as in Synthesis Example 2-1 except that the intermediate compound represented by formula (2-B) {a:34} obtained in Synthesis Example 1-3 was used.
[0206] Synthesis Example 2-3 1 The assignment results of H NMR analysis are shown below.
[0207] 1 H NMR (DMSO-d6): δ=0.0ppm (Si- CH 3 ), 0.5ppm(Si- CH 2 -), 1.5 to 1.8 ppm (-CH 2 - CH 2 -CH 2 -), 1.9ppm(-C-CH 3 ), 3.2ppm(N- CH 3 ), 3.3 to 3.8 ppm (O- CH 2 -, N- CH 2 -), 4.0 to 4.5 ppm (C(=O)-O- CH 2 -,-PO- CH 2 -), 5.6ppm, 6.1ppm( CH 2 =C-)
[0208] <Evaluation method>
[0209] Each evaluation item will be described. The compositions, polymers, and contact lenses in Comparative Examples outside the scope of the present invention are also simply referred to as compositions, polymers, and contact lenses as in Examples.
[0210] [a. Transparency of the composition]
[0211] The transparency was evaluated by visual inspection according to the following criteria: The smaller the score, the better the transparency.
[0212] Transparent: Fraction [0]
[0213] Translucency: Fraction [1]
[0214] Turbidity: Fraction [2]
[0215] [b. Transparency of contact lenses]
[0216] The contact lens according to the present invention was manufactured to have a thickness of 100±30 μm, and the transparency was evaluated by visual observation according to the following criteria: A smaller score indicates better transparency.
[0217] Transparent: Fraction [0]
[0218] Translucency: Fraction [1]
[0219] Turbidity: Fraction [2]
[0220] [c.WBUT]
[0221] The wettability of the contact lens is evaluated using the water film breakup time (WBUT). Using tweezers or the like, slowly remove the contact lens from the physiological saline and measure the time until the water film breaks. This time is defined as WBUT and is evaluated according to the following criteria. The smaller the score, the better the wettability (hydrophilicity) of the contact lens.
[0222] More than 10 seconds: Score [0]
[0223] More than 5 seconds and less than 10 seconds: Score [1]
[0224] Less than 5 seconds: Fraction [2]
[0225] [d. Moisture content]
[0226] The moisture content of the contact lenses was measured by the method described in ISO-18369-4 and evaluated according to the following criteria: The smaller the score, the better the moisture content.
[0227] 40% or more and less than 55%: Score [0]
[0228] 30% or more and less than 40%, or more than 55% and less than 60%: Score [1]
[0229] Less than 30% or more than 60%: Fraction [2]
[0230] [e. Oxygen permeability coefficient]
[0231] The oxygen permeability coefficient of the contact lens was measured according to the method described in ISO 18369-4 and evaluated according to the following criteria.
[0232] The smaller the score, the better the oxygen permeability coefficient. Specifically, the oxygen permeability coefficient was measured according to the polarographic measurement method described in ISO18369-4. For the measurement, an O2 Permeometer Model 201T manufactured by Rehder Development Company was used. The lens thickness was plotted on the x-axis, and the inverse of the measured current value was plotted on the y-axis, and the oxygen permeability coefficient was calculated based on the inverse of the slope of the regression line. Note that the unit (barrer) of the oxygen permeability coefficient is ×10 -11 (cm 2 / sec)·(mLO 2 / mL×mmHg).
[0233] 70 and above: Score [0]
[0234] 50 or more and less than 70: Score [1]
[0235] Less than 50: Fraction [2]
[0236] [f. Antifouling properties]
[0237] As the evaluation of antifouling property, coatability was evaluated according to the following procedure.
[0238] ○Coating performance evaluation method
[0239] Sudan Black B (0.05 g) was dissolved in 10 g of tocopherol, and 40 g of liquid paraffin was added thereto and mixed uniformly. This was used as a staining solution. The evaluation lens was taken out from the glass vial, the moisture on the lens surface was wiped off, and the lens was immersed in 1 mL of the staining solution for 5 minutes. The contact lens was taken out, and the excess staining solution was removed with physiological saline and a standard cloth moistened with physiological saline. The contact lens dyed with the staining solution was immersed in 1.5 mL of physiological saline, and its absorbance at 600 nm was measured. The absorbance of the contact lens before staining was defined as A 0 , and the absorbance of the contact lens after dyeing is defined as A 1 .
[0240] The increase in absorbance due to dyeing was calculated according to the following equation (A), and the coatability was evaluated by a score based on the following criteria.
[0241] Sudan Black B is hydrophobic and adsorbs to hydrophobic substances, and thus easily adsorbs to hydrophobic lens surfaces or hydrophobic spots. Therefore, a smaller absorbance, i.e., a smaller score, indicates that the lens surface is coated with a hydrophilic polymer and has better coatability.
[0242] Absorbance = A 1 -A 0 Equation (A)
[0243] Less than 0.05: Score [0]
[0244] 0.05 or more and less than 0.10: Score [1]
[0245] 0.10 or more and less than 0.20: Score [2]
[0246] 0.20 and above: Score [3]
[0247] [Example 1]
[0248] In a container, 0.50 g (10.0 mass%) of MPC, 2.00 g (40.0 mass%) of the compound in Synthesis Example 2-1, 1.00 g (20.0 mass%) of SiGMA and 1.10 g (22.0 mass parts) of HBMA were mixed and stirred at room temperature until MPC was dissolved. In addition, 0.375 g (7.0 mass%) of NVP, 0.025 g (1.0 mass%) of TEGDMA and 0.025 g (0.5 mass part) of AIBN were added to the container, and the mixture was stirred at room temperature until uniform to obtain a composition.
[0249] The composition is filled into a compartment of 25mm×70mm×0.1mm, which is formed by sandwiching two polypropylene plates using a 0.1mm thick polyethylene terephthalate sheet as a spacer. The lens mold filled with the composition is loaded into an oven, and the atmosphere in the oven is replaced with nitrogen. Then, the temperature in the oven is raised to 80°C and kept at 80°C for 12 hours to polymerize the composition and manufacture a polymer. The polymer is taken out from the lens mold to obtain a polymer having a contact lens shape. The polymer is immersed in 100mL of a 50% by mass 2-propanol aqueous solution for 4 hours, and then immersed in 100mL of ion exchange water for 4 hours to remove unreacted substances, etc., thereby purifying the polymer. According to ISO-18369-3, the purified polymer is immersed in physiological saline and swelled (hydrated) to manufacture silicone hydrogel contact lenses. The contact lenses are divided into sizes and shapes suitable for each item in the above evaluation, and each evaluation is performed. The mixing ratio, polymerization conditions and evaluation results of each component in the composition are shown in Table 1.
[0250] [Examples 2 to 4]
[0251] A silicone hydrogel contact lens was manufactured in the same manner as in Example 1, except that the mixing ratio of the components in the composition and the polymerization conditions were as shown in Table 1. The contact lenses in Example were evaluated in the same manner as in Example 1.
[0252] Table 1 shows the results.
[0253] Note that, regarding Example 4, the irradiation was performed by using a UV-LED irradiator (irradiation light wavelength: 405 nm) at room temperature with UV light at 1.5 mW / cm 2 The composition was polymerized by irradiating with an irradiance of 1000 nm for 30 minutes to obtain a polymer.
[0254] [Comparative Examples 1 to 4]
[0255] The same operation as in Example 1 was performed except that the mixing ratio of the components in the composition and the polymerization conditions were as shown in Table 2. The contact lenses in Comparative Examples were evaluated in the same manner as in Example 1. The mixing ratio of the components in the composition, the polymerization conditions and the evaluation results are shown in Table 2.
[0256] Comparative Example 1 is different from the Examples in that it does not contain a phosphorylcholine group-containing silicone macromonomer and has a high content of an amide group-containing hydrophilic monomer. Note that since the transparency of the composition was evaluated as "2", a polymer was not subsequently produced.
[0257] Comparative Example 2 differs from the Example in that it does not contain a phosphorylcholine group-containing silicone macromer. Note that since the transparency evaluation of the polymer was "2", subsequent evaluations such as WBUT were not performed.
[0258] The difference between Comparative Example 3 and the Example is that the content of the organosilicon macromolecular monomer containing phosphorylcholine group is low.
[0259] [Table 1]
[0260]
[0261] [Table 2]
[0262]
[0263] [Evaluation of Examples]
[0264] The evaluation results in Table 1 will be described below.
[0265] All Examples 1 to 4 gave a score of "0" in the evaluation of composition uniformity and a score of "0" in the evaluation of transparency of the polymerization product, indicating that the composition and polymerization product according to the present invention exhibit very good compatibility with the hydrophilic monomer or hydrophilic polymer.
[0266] All Examples 1 to 4 were given a score of "0" in the evaluation of wettability (hydrophilicity), indicating that the contact lenses according to the present invention exhibit very good hydrophilicity.
[0267] All Examples 1 to 4 were given a score of "0" in the evaluation of the water content, indicating that the contact lenses according to the present invention exhibited very good water content.
[0268] For oxygen permeability, all Examples 1 to 3 were given a score of "0" and Example 4 was given a score of "1". The contact lenses according to the invention exhibit very good or good oxygen permeability.
[0269] In the evaluation of antifouling properties, all Examples 1, 2 and 4 were given a score of "0", and Example 3 was given a score of "1". The contact lenses according to the invention exhibit very good or good antifouling properties (coatability).
[0270] It can be seen from the above results that the contact lenses according to the present invention simultaneously exhibit very good hydrophilicity, very good water content, very good or good oxygen permeability and very good or good antifouling property (coatability) without surface treatment, and therefore can provide excellent wearing comfort to the wearer.
[0271] [Evaluation of Comparative Example]
[0272] Comparative Example 3 was given a score of "3" in the evaluation of wettability (hydrophilicity) and a score of "2" in the evaluation of antifouling property (coatability), indicating that the contact lens in Comparative Example 3 exhibited neither hydrophilicity nor antifouling property (coatability).
[0273] Industrial Applicability
[0274] The present invention can provide a monomer composition for contact lenses and a contact lens obtained from the composition, which can simultaneously exhibit very good surface hydrophilicity, very good water content, good coatability and good oxygen permeability.
[0275] Although the present invention has been described in detail and with reference to specific embodiments thereof, it will be apparent to one skilled in the art that various changes or modifications can be made to the present invention without departing from the spirit and scope of the present invention.
[0276] This application is based on the Japanese patent application filed on September 15, 2022 (Japanese patent application number 2022-146674), the contents of which are incorporated herein by reference.
Claims
1. A monomer composition for contact lenses, comprising: (A) a phosphorylcholine group-containing monomer represented by the following formula (1); (B) a phosphorylcholine group-containing organosilicon macromer represented by the following formula (2); (C) an organosilicon monomer or macromer other than the organosilicon macromer containing a phosphorylcholine group represented by formula (2); (D) one or more hydroxyl-containing hydrophilic monomers selected from the group consisting of hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyethyl (meth)acrylamide, ethylene glycol monovinyl ether, glyceryl methacrylate and diethylene glycol monovinyl ether; (E) one or more amide group-containing hydrophilic monomers, wherein the one or more amide group-containing hydrophilic monomers are selected from the group consisting of N-vinyl-2-pyrrolidone, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-methyl-N-vinylacetamide and N-vinylacetamide; and (F) a cross-linking agent, wherein With respect to 100% by mass of the total amount of components (A) to (F) in the composition according to the present invention, the content of component (A) is 5% to 25% by mass, the content of component (B) is 10% to 60% by mass, the content of component (C) is 5% to 40% by mass, the content of component (D) is 5% to 40% by mass, the content of component (E) is 0% to 20% by mass, and the content of component (F) is 0% to 2.5% by mass, [Chemical formula 1] In formula (1), R 1 is H or CH3, and W 1 O or NR 4 , where R 4 is H or an alkyl group having 1 to 4 carbon atoms, [Chemical formula 2] In formula (2), R 1 is H or CH3, W 1 O or NR 4 , where R 4 is H or an alkyl group having 1 to 4 carbon atoms, a is an integer from 1 to 100, and A 1 It is expressed by formula (3): [Chemical formula 3] -YZ…Formula (3) In formula (3), Y is represented by formula (4), and Z is a phosphorylcholine group represented by formula (6), [Chemical formula 4] [In the formula, b is 2 or 3, and c is 0 or 1], [Chemical formula 5] 2. The monomer composition for contact lenses according to claim 1, wherein The component (C) is a hydroxyl-containing organic silicon monomer represented by the following formula (9) or formula (10), [Chemical formula 6] [Chemical formula 7] 3. The monomer composition for contact lenses according to claim 1 or 2, wherein: In the monomer composition for contact lenses comprising the components (A) to (F), the proportion of phosphorylcholine groups is 10% by mass or more, and the proportion of silicon is 10% or more.
4. A polymer for contact lenses, which is a polymer of the monomer composition for contact lenses according to claim 1 or 2.
5. A contact lens comprising: The hydrate of the polymer for contact lenses according to claim 4.
6. The contact lens according to claim 5, wherein: The oxygen permeability coefficient Dk of the contact lens is 50×10 -11 (cm 2 / sec)·(mLO2 / mL×mmHg) or above.
Citation Information
Patent Citations
Contact lens with hydrophilic layer
JP2018022174A
Information processing system, information processing apparatus, information processing method, and program
JP2022146674A
Phosphorylcholine group-containing polysiloxane monomer
WO2019194264A1
Monomer composition for contact lens, polymer thereof, contact lens, and production method thereof
WO2020054711A1